Odpowiedź :
[tex](2 \frac{1}{6} - 1 \frac{1}{3}) \times 2 \frac{2}{5} = ( \frac{13}{6} - \frac{4}{3} ) \times \frac{12}{5} = ( \frac{13}{6} - \frac{8}{6} ) \times \frac{12}{5} = \frac{5}{6} \times \frac{12}{5} = \frac{12}{6} = 2[/tex]
[tex]2 \frac{2}{7} \times 7 - {(3 \frac{1}{2}) }^{2} = \frac{16}{7} \times 7 - \frac{49}{4} = 16 - 12 \frac{1}{4} = 3 \frac{3}{4} [/tex]
[tex]( {2 \frac{1}{2} - 1 \frac{1}{3} ) }^{2} - ( { \frac{5}{6} )}^{2} = ( { \frac{5}{2} - \frac{4}{3}) }^{2} - \frac{25}{36} = ( { \frac{15}{6} - \frac{8}{6} ) }^{2} - \frac{25}{36} = {( \frac{7}{6}) }^{2} - \frac{25}{36} = \frac{49}{36} - \frac{25}{36} = \frac{24}{36} = \frac{2}{3} [/tex]
[tex] {(1 \frac{1}{2} )}^{3} - {( \frac{2}{3}) }^{3} - \frac{1}{5} \times 2 \frac{1}{6} = ( { \frac{3}{2}) }^{3} - \frac{8}{27} - \frac{1}{5} \times \frac{13}{6} = \frac{27}{8} - \frac{8}{27} - \frac{13}{30} = \frac{729}{216} - \frac{64}{216} - \frac{13}{30} = \frac{665}{216} - \frac{13}{30} = \frac{19950}{6480} - \frac{2808}{6480} = \frac{17142}{6480} = 2 \frac{4182}{6480} = 2 \frac{2091}{3240} = 2 \frac{697}{1080} [/tex]
Odpowiedź:
(2 1/6 - 1 1/3) * 2 2/5 = (1 7/6 - 1 2/6) * 12/5 = 5/6 * 12/5 = 2
2 2/7 * 7 - (3 1/2)² = 16/7 * 7 - (7/2)² = 16 - 49/4 = 16 - 12 1/4 = 3 3/4
(2 1/2 - 1 1/3)² - (5/6)² = (2 3/6 - 1 2/6)² - 25/36 = (1 1/6)² - 25/36 = (7/6)² - 25/36 =
= 49/36 - 25/36 = 24/36 = 2/3
(1 1/2)³ - (2/3)³ - 1/5 * 2 1/6 = (3/2)³ - (2/3)³ - 1/5 * 13/6 = 27/8 - 8/27 - 13/30 =
= 3 3/8 - 8/27 - 13/30 = 3 81/216 - 64/216 - 13/30 = 3 17/216 - 13/30 = 3 170/2160 - 936/2160 = 2 2330/2160 - 936/2160 = 2 1394/2160 = 2 697/1080
Szczegółowe wyjaśnienie: